The effectiveness of simulation game on nursing students’ surgical nursing knowledge: a quasi-experimental study - Koivisto Jaana-Maija; Buure Tuija; Engblom Janne; Rosqvist Kristiina; Haavisto Elina (Elsevier, 2025)
Student nurses need diverse learning experiences throughout their studies to learn surgical nursing. Interactive virtual simulations for hybrid education in the COVID-19 postpandemic era provide new opportunities to learn knowledge through practical patient scenarios. The aim of this study was to evaluate the effectiveness of a simulation game on nursing students’ surgical nursing knowledge. A quasi-experimental design was used, including a pre- and post-test and experimental (simulation game) group (n = 140) and a control (theoretical self-study material) group (n = 136). The level of surgical nursing knowledge was assessed with the surgical nursing knowledge (SNK) test. The data were collected in three universities of applied sciences in Finland. Both groups had better surgical nursing knowledge after the intervention than before. The change of surgical nursing knowledge was greater in the experimental group than in the control group. The simulation game was an effective approach to learning surgical knowledge. Simulation games as an interactive and motivating tool may add value in hybrid education by combining theoretical pre- and postoperative nursing care content and practical skills.